Composition and Protein Precipitation Capacity of Condensed Tannins in Purple Prairie Clover (Dalea purpurea Vent.) - Huang, Qianqian; Hu, Tianming; Xu, Zhongjun; Jin, Long; McAllister, Tim A.; Acharya, Surya; Zeller, Wayne E.; Mueller-Harvey, Irene; Wang, Yuxi (Frontiers in Plant Science, 2021)
The objectives of this study were to determine the concentration and chemical structure of condensed tannins (CT) in different tissues of purple prairie clover (PPC; Dalea purpurea Vent.) at different maturities and to determine their protein-precipitating capacity. The structural compositions of CT were elucidated after thiolysis with benzyl mercaptan followed by high-performance liquid-chromatography and 1H−13C HSQC NMR spectroscopy. Results indicated that PPC flowering heads contained the highest CT concentration. Purple prairie clover CT consisted mainly of epicatechin (EC) and epigallocatechin (EGC) subunits. Condensed tannins from leaves were composed of more EC and less EGC than CT from stems and flowering heads at both early flowering and late flowering head stages. The mean degree of polymerization was the highest for CT from stems and increased with maturity. Condensed tannins isolated from PPC leaves at the early flowering head stage exhibited the greatest biological activity in terms of protein precipitation. Overall, condensed tannins in PPC were predominantly procyanidins and the concentration and composition varied among plant tissues and with maturity.